Evidence-based interventions and nurse-sensitive outcomes in district nursing care: A systematic review - J.D. Veldhuizen; T.B. Hafsteinsdóttir; M.C. Mikkers; N. Bleijenberg; M.J. Schuurmans (Elsevier, 2021)
Background: Measuring nursing interventions and nurse-sensitive outcomes in a standardized manner is essential because it provides insight into the quality of delivered care. However, there is currently no systematic overview of the interventions conducted by district nurses, the evidence for the effects of these interventions, or what nurse-sensitive outcomes should be measured. Objective: 1) To provide an overview of interventions for community-living older people evaluated in district nursing care and evidence for the effects of these interventions and 2) to identify the nurse-sensitive outcomes that are used to evaluate these district nursing care interventions, how these outcomes are measured, and in which patient groups they are applied. Design: A systematic review of the literature. Setting: District nursing care. Data sources: MEDLINE, CINAHL, PsycInfo, and EMBASE. Methods: Only experimental studies evaluating district nursing care interventions for communkity-living older people were included. A data extraction form was developed to extract the study characteristics and evaluate interventions and nurse-sensitive outcomes. The methodological quality of the included studies was reviewed using the 13-item critical appraisal tool for randomized controlled trials by the Joanna Briggs Institute. Results: A total of 22 studies were included. The methodological quality of the studies varied, with scores ranging from 6 to 11 on a scale of 0-13. The 22 interventions identified were heterogeneous with respect to intervention components, intervention delivery, and target population. The 44 outcomes identified were grouped into categories following the Nursing Outcome Classification and were measured in various ways and at various times. Conclusion: This is the first systematic review summarizing the evidence for the effectiveness of nurse-led interventions conducted by district nurses on community-living older people. It is unclear what interventions are effective and what outcomes should be used to substantiate district nursing care effectiveness. Because only studies with experimental designs were included, this analysis may provide an incomplete assessment of the effectiveness of interventions in district nursing care. Therefore, it is highly necessary to produce methodologically strong evidence through research programs focusing on district nursing care.